SERTIFIKASI HAK MILIK ATAS TANAH YANG BERASAL DARI BEKAS HAK MILIK TANAH ADAT - Eddie; Hadin Muhjad; Suprapto (Collegium Studiosum Journal, 2023)
After the UUPA came into effect, all land rights throughout Indonesia were subject to land law regulated by the UUPA, in fact in society there were still rights to land from customary law, so that the conversion was carried out from an atmosphere of customary law to become UUPA. For legal certainty over land rights, the Head of the National Land Agency issued a special policy on customary land registration procedures.